African spirituality: unearthing beliefs and practices for the helping professions - Singh, Charlene; Bhagwan, Raisuyah (Social Work, 2020)
Empirical work related to African spirituality in the social sciences, particularly within the social work context, is sparse. It is crucial that practitioners have a deeper understanding of the beliefs and practices that can support therapeutic goals in practice. Using qualitative research methodology, 20 child and youth care students at a selected university in South Africa, who are proponents of African spirituality, were interviewed with regards to their beliefs and practices. The major objective was to gain a richer insight into African spirituality and those African healing methodologies considered most relevant to child and youth care practice. Prayer to the ancestral spirits, sacrificial rituals and music were considered to be some of the most important practices identified that could guide both child and youth care practice and social work.
free